Transforming Bronsted Acid to Lewis Acid on ZSM-5 Disproportionation Catalyst Before and After Loading AlCl3 - Xu, Wen-Yuan; Liu, Yi-Ping; Zhou, Jie-Xia; Hu, Lin; Hong, San-Guo (Asian Journal of Chemistry, 2015)
The study on disproportionation reaction of methyltrichlorosilane and trimethylchlorosilane to generate dimethyldichlorosilane has been carried out by B3LYP/6-311++G** method. The results showed that the active sites on ZSM-5 pre-loading AlCl3 is Brønsted acid. The activation energy of rate determining step in main reaction was 166.98 (channel a) and 202.68 (channel b) kJ mol-1. After loading AlCl3, ZSM-5 active catalyst was Lewis acid, the activation energy of rate determining step in main reaction was 92.68 kJ mol-1. The calculation results match with the experimental results.